Enhancer RNA Transcriptome‐Wide Association Study Reveals a Distinctive Class of Pan‐Cancer Susceptibility eRNAs - Wenyan Chen; Zeyang Wang; Yinuo Wang; Jianxiang Lin; Shuxin Chen; Hui Chen; Xuelian Ma; Xudong Zou; Xing Li; Yangmei Qin; Kewei Xiong; Xixian Ma; et al. (Advanced Science)
Abstract Many cancer risk variants are located within enhancer regions and lack sufficient molecular interpretation. Here, we constructed the first comprehensive atlas of enhancer RNA (eRNA)‐mediated genetic effects from 28 033 RNA sequencing samples across 11 606 individuals, identifying 21 073 eRNA quantitative trait loci (eRNA‐QTLs) significantly associated with eRNA expression. Mechanistically, eRNA‐QTLs frequently altered binding motifs of transcription factors. In addition, 28.48% of cancer risk variants are strongly colocalized with eRNA‐QTLs. A pan‐cancer eRNA‐based transcriptome‐wide association study is conducted across 23 major cancer types, identifying 626 significant cancer susceptibility eRNAs predicted to modulate cancer risk via eRNA, from which 54.90% of the eRNA target genes are overlooked by traditional gene expression studies, and most are essential for cancer cell proliferation. As proof of principle validation, the enhancer functionality of two newly identified susceptibility eRNAs, CCND1e and SNAPC1e, is confirmed through CRISPR inhibition and shRNA‐mediated knockdown, resulting in a marked decrease in the expression of their respective target genes, consequently suppressing the proliferation of prostate cancer cells. The study underscores the essential role of eRNA in unveiling new cancer susceptibility genes and establishes a strong framework for enhancing our understanding of human cancer etiology.